Pengaruh Gaya Kepemimpinan dan Lingkungan Kerja terhadap Kepuasan Kerja Karyawan dengan Komunikasi sebagai Variabel Pemediasi pada PT. Harapan Sawit Lestari (HSL) Cargill Betivau Estate - Ibnu Rizkiawan; Jajuk Herawati; Ignatius Soni Kurniawan (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2023)
This study aims to determine the effect of leadership style and work environment on employee job satisfaction with communication as a mediating variable at PT. Harapan Sawit Lestari (HSL) Cargill Betivau Estate. This research is a quantitative research and primary data is taken using a questionnaire taken by accidental sampling on 74 respondents. Sampling using the Slovin formula. Data were collected through direct surveys and then processed using multiple linear regression analysis. The results showed that leadership style had a positive and significant effect on communication. The work environment has no significant effect on communication. Leadership style, work environment, and communication partially have a positive and significant effect on employee job satisfaction. Communication mediates the effect of leadership style on employee job satisfaction, but communication does not mediate the effect of the work environment on employee job satisfaction. Keywords: leadership style; employee job satisfaction; communication; work environment.